DAKWAH ISLAM DAN TANTANGAN MEDIA GLOBAL - Mahfudlah Fajrie (Islamic Review: Jurnal Riset dan Kajian Keislaman, 2013)
The present culture in the western world continues to hit the Islamic world through their modern and sophisticated information technology. On the other hand, Islam still stuck to its ethics in propagation activity that refers to the western civilization. The problems of propagation models actually give serious influence to either Islam or the West in particular. Therefore, through this study, it is important for Muslims to determine the strategies, methods and mission plan to anticipate the future globalization challenges. The explanation of this article is supported by propagation model approach used by both the civilizations. The ways for developing missions of propagation in the globalization era, an in-depth and comprehensive concepts and strategies are required. This is through observations based on the needs and conditions of the present societies, establishment of the Khilafah organizations, propagation by revealing the true nature of Islam, re-evaluation of the propagation activities, translating the western works to expand the knowledge and learn the history of Islam as reference material of propagation. Propagation can be used as the system changes of people's lives, politics, economics, culture and law that exist in a society. It also can be used as guidance of life so that people do not lose their idealism.